Pragmatik dalam Bahasa: “Melatih Kemampuan Berkomunikasi untuk Siswa SD” - Ritonga, Maharani; Ritonga, Mara Untung; Ansari, Khairil (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
The background to this research is the importance of developing effective communication skills from an early age, especially considering the role of communication in social and academic life. Pragmatic abilities, which include understanding and using language in social contexts, are the main focus in efforts to improve elementary school students' communication skills. This research aims to examine the importance of teaching pragmatics in language to elementary school (SD) students in order to improve communication skills and evaluate the impact of learning pragmatics towards students' social interactions. .The methods used include observations, interviews, and pedagogical interventions in the form of role plays, group discussions, and situational exercises designed to increase students' pragmatic awareness. The research results show that students become better able to understand the context of a conversation, adapt their language style to the person they are talking to, and show an increase in self-confidence when communicating. students who were involved in pragmatics training showed significant improvements in their communication abilities, both in speaking and listening skills. So it can be concluded that the integration of pragmatics teaching in the language curriculum at elementary school level can make an important contribution in forming better communication skills in students. The implementation of learning strategies that focus on real situations and social interactions is recommended in the curriculum to optimize the development of students' communication skills from an early age.